The use of hydrotherapy, walking, and lumbosacral massage as non-pharmacological methods used for pain relief in labor and delivery (Research, Society and Development, 2022)
Objective: To verify the effectiveness of non-pharmacological methods (NFM) in reducing pain during labor and delivery, by encouraging obstetric nursing professionals, specifying low-cost therapeutic methods. Method: This was an integrative review, with articles available online, in a time frame between 2014 and 2022. The sample consisted of 05 national articles, where the most recurrent and low-cost MNF for institutions were selected, arranged by through categories and synthesized according to the evidence of each publication. Results: Hydrotherapy was the NFM most used by parturients as a form of pain relief, followed by breathing, lumbosacral massage and walking as other most recurrent tools. There was a high rate of use of acupuncture variations. A single study cited rebozo and spinning babies. Conclusion: The use and acceptance of NFM to relieve pain during labor, favoring natural childbirth and promoting the pregnant woman's participation in the physiological process of childbirth should be encouraged by obstetric nursing.